Marketing in Postmodern India: Bulgari Meets Bollywood - Atwal, Glyn; Williams, Alistair (Indian Journal of Marketing, 2008)
The implications of postmoderism within an Indian marketing context has received little, or no, attention from academics and practitioners alike. This is surprising in light of the impact of globalisation on consumer attitudes and behaviour in a fast changing Indian society. In order to examine the extent postmodern conditions are relevant in Indian society and to discuss their implications for contemporary marketing strategies, this paper uses a framework developed by Firat and Venkatesh (1993). The findings show that although the origins of postmodernism are embedded in western culture, contemporary Indian society is embracing postmodernism. Marketing strategies need to be increasingly developed through a postmodern orientation. New approaches need to be considered in order to capitalise on the opportunities offered by the new generation of consumers. Experiential marketing views consumers as emotional beings in which brands engage with consumers through deep, meaningful and tangible experiences. Those who market experientially will achieve a sustainable competitive advantage. Innovative experience design will need to become a key component of postmodern marketing in contemporary India.